2021
DOI: 10.3390/su13073866
|View full text |Cite
|
Sign up to set email alerts
|

Two Sides of the Same Coin. University-Industry Collaboration and Open Innovation as Enhancers of Firm Performance

Abstract: Open innovation is proved to be determinant in the rationalization of sustainable innovation ecosystems. Firms, universities, governments, user communities and the overall environment are called to contribute to this dynamic process. This study aims to contribute to a better understanding of the impact of open innovation on firms’ performance and to empirically assess whether university-industry collaborations are complementary or substitutes for this activity. Primary data were collected from a survey encompa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 63 publications
0
30
0
Order By: Relevance
“…The example of outbound open innovation is presented in Table VII. [13], [26], [32], [49], [55] Spin-off [13], [26], [32], [50], [53] Open sourcing [13], [26], [45], [48],…”
Section: ) Outbound Open Innovationmentioning
confidence: 99%
See 3 more Smart Citations
“…The example of outbound open innovation is presented in Table VII. [13], [26], [32], [49], [55] Spin-off [13], [26], [32], [50], [53] Open sourcing [13], [26], [45], [48],…”
Section: ) Outbound Open Innovationmentioning
confidence: 99%
“…Reference Inbound Open Innovation [13], [26] [27], [28], [33], [34], [37], [38], [39], [40], [41], [42], [44]. [46], [47], [48], [49], [50],…”
Section: Table IX Open Innovation Manifest Open Innovation Manifestmentioning
confidence: 99%
See 2 more Smart Citations
“…Companies operating in the same sector can benefit from knowledge spillovers within a geographic location, and university-industry collaborations can solidify such geographic industrial clusters [ 129 ]. CRADAs are inherently collaborative, and collaborations based on clear shared goals and honest, open dialogue enhance university-firm performance [ 130 , 131 ]. Evidence from comparative case studies reported in the literature and our quantitative analyses in this study suggests that the same is likely true for government-firm collaborations [ 55 , 132 , 133 ].…”
Section: Discussionmentioning
confidence: 99%